Pembentukan Karakter Melalui Pembelajaran PAKEM - Andriany, Liesna (Universitas Islam Sumatera Utara, 2013)
ABSTRACTUniversity is aplace to create the children of nation in to the qualified human, intellectual, virtuous character which have been the slogan and logo of education. To achieve these educational goals,learning is the core of educational process. Achievement of quality professional learning is theresponsibility of a teacher. There fore, a holistic systematicis necessary as an effort to increase thequality and character of sciencethat canbe applied through innovative and constructive learningmodel. Implications of applying the model PAKEM which integrates with character valuesindirectly will develop the character quality of graduates, ready-made, self-reliant, resilient,creative, innovative and well characterized. Key words: character, PAKEM